Strategy beyond markets - De Figueiredo, John M.; Lenox, Michael; Oberholzer-Gee, Felix; Vanden Bergh, Richard G. (Emerald, 2016)
Strategy Beyond Markets examines how the strategies employed by firms affect long run value. Scholars in this field focus their attention on firm interactions with entities other than the firm's primary market stakeholders. These stakeholders include international NGOs, environmental groups, local communities, regulators, politicians and the courts. This book is organized around three themes: Public politics, private politics, and integrated political strategy. In public politics, firms use sophisticated instruments (e.g., campaign funding, committee participation) to influence local, national, and international political environments. In private politics, firms work closely with NGOs and other special interest groups to preempt unfavorable policy, react swiftly to crises, and proactively develop socially responsible strategies. Additionally, firms that are heavily influenced by politics are more likely to craft integrated political strategy as part of a more comprehensive plan. This special issue comprises papers from preeminent scholars including David Baron, Jean-Philippe Bonardi, Daniel Diermeier, Thomas Lyon, John Maxwell, Ken Shotts, and Dennis Yao.
Keywords: Business & Economics -- Strategic Planning.; Business strategy.; Business planning.; Strategic planning.; Organizational behavior.; elektronické knihy; electronic books